I-ω^*-Continuous and I-ω^*- Open Functions - Hessean, Nawroz O.; Darwesh, Halgwrd M.; Namiq, Sarhad F. (Iraqi Journal of Science, 2024)
In ideal topological space, we define and study a new class of functions known as I-ω^*-continuous functions by using  I-ω^*-open sets. This idea is stronger than each of the classes (ω-continuous,  ωb-continous,  α-I_ω-continuous,  pre-I_ω-continuous,  β-I_ω-continuous, faintly- ω-continuous, slightly- ω-continuous, 〖 I〗_ω-c-continuous).  Furthermore, relationships between this class and other relevant classes of functions are investigated, and some characterizations of this new class of functions are studied. Finally, we introduce the  I-ω^*- open function as an extension of the ω- open function through I-ω^*-open sets, and some results are provided.